2004
DOI: 10.1080/j.1440-1614.2004.01450.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Early Psychosis Service Provision: A File Audit

Abstract: The services increased their provision of "guideline concordant" care for early psychosis. The audit proved useful to monitor performance, to demonstrate improvements in care and to identify those areas of service provision and documentation in need of improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Clients were excluded if they had a hospital admission only, and were not followed up by community services in Northern Sydney. These criteria contrast with those of the 1999 cohort from Gorrell et al (2004) which included all clients who received any in-patient or community treatment in the area over a six month period (N ¼ 74).…”
Section: Samplementioning
confidence: 95%
See 4 more Smart Citations
“…Clients were excluded if they had a hospital admission only, and were not followed up by community services in Northern Sydney. These criteria contrast with those of the 1999 cohort from Gorrell et al (2004) which included all clients who received any in-patient or community treatment in the area over a six month period (N ¼ 74).…”
Section: Samplementioning
confidence: 95%
“…Aspects of assessment such as routine physical examinations (particularly assessment of weight), formal assessments of involuntary movements and comprehensive re-assessments of symptoms at three-to-six months were also recommended for improvement. Gorrell et al (2004) observed that some file audit indicators might provide an underestimate of service provision when interventions were not documented in the file or could not be reliably identified by auditors. It is likely that some services, such as group programs, were underestimated by using the file audit methodology alone and additional sources may be required to ensure accurate data regarding these aspects of service provision (Schachter & Kleinman, 1998;Young, Sullivan, Burnam, & Brook, 1998).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations